Functional Effects of Intervening Illnesses and Injuries After Hospitalization for Major Surgery in Community-living Older Persons. Issue 5 (14th May 2021) - Gill, Thomas M.; Han, Ling; Gahbauer, Evelyne A.; Leo-Summers, Linda; Murphy, Terrence E.; Becher, Robert D.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To evaluate the functional effects of intervening illnesses and injuries, that is, events, in the year after major surgery. Background: Intervening events have pronounced deleterious effects on functional status in older persons, but have not been carefully evaluated after major surgery. Methods: From a cohort of 754 community-living persons, aged 70+ years, 317 admissions for major surgery were identified from 244 participants who were discharged from the hospital. Functional status (13 activities) and exposure to intervening hospitalizations, emergency department (ED) visits, and restricted activity were assessed each month. Comprehensive assessments (for covariates) were completed every 18 months. Results: In the year after major surgery, exposure rates (95% CI) per 100-person months to hospitalizations, ED visits, and restricted activity were 10.0 (8.0–12.5), 3.9 (2.8–5.4), and 12.3 (10.2–14.8) for functional recovery and 7.2 (6.1–8.5), 2.5 (1.9–3.2), 11.2 (9.8–12.9) for functional decline. Each of the 3 intervening events were independently associated with reduced recovery, with adjusted hazard ratios (95% CI) of 0.20 (0.09–0.47), 0.35 (0.15–0.81), and 0.57 (0.36–0.90) for hospitalizations, ED visits, and restricted activity. For functional decline, the corresponding odds ratios (95% CI) were 5.68 (3.87–8.33), 1.90 (1.13–3.20), and 1.30 (0.96–1.75). The effect sizes for hospitalizations and ED visits were larger than those for the covariates. Conclusions: Intervening illnesses/injuries are common in the year after major surgery, and those leading to hospitalization and ED visit are strongly associated with adverse functional outcomes, with effect sizes larger than those of traditional risk factors.